A comparison of relative-frequency and threshold-hunting methods to determine stimulus intensity in transcranial magnetic stimulation - Silbert, B.I.; Patterson, H.I.; Pevcic, D.D.; Windnagel, K.A.; Thickbroom, G.W. (Clinical neurophysiology, 2013)
► Evaluated the latest International Federation of Clinical Neurophysiology recommendation for determining motor threshold. ► Adaptive threshold-hunting (PEST) determined threshold with fewer stimuli and with comparable results to the Rossini–Rothwell relative-frequency method. ► Equivalent results are obtained when targeting a supra-threshold MEP amplitude (1mV). Stimulation intensity (SI) in transcranial magnetic stimulation is commonly set in relation to motor threshold (MT), or to achieve a motor-evoked potential (MEP) of predefined amplitude (usually 1mV). Recently, IFCN recommended adaptive threshold-hunting over the previously endorsed relative-frequency method. We compared the Rossini–Rothwell (R–R) relative-frequency method to an adaptive threshold-hunting method based on parameter estimation by sequential testing (PEST) for determining MT and the SI to target a MEP amplitude of 1mV (I1mV). In 10 healthy controls we determined MT and I1mV with R–R and PEST using a blinded crossover design, and performed within-session serial PEST measurements of MT. There was no significant difference between methods for MT (52.6±2.6% vs. 53.7±3.1%; p=0.302; % maximum stimulator output; R–R vs. PEST, respectively) or I1mV (66.7±3.0% vs. 68.8±3.8%; p=0.146). There was strong correlation between R–R and PEST estimates for both MT and I1mV. R–R required significantly more stimuli than PEST. Serial measurements of MT with PEST were reproducible. PEST has the advantage of speed without sacrificing precision when compared to the R–R method, and is adaptable to other SI targets. Our results in healthy controls add to increasing evidence in favour of adaptive threshold-hunting methods for determining SI.